Exploitation of Compartmentalization in RAFT Miniemulsion Polymerization to Increase the Degree of Livingness. Issue 18 (5th February 2019) - Khan, Murtaza; Guimarães, Thiago R.; Zhou, Dewen; Moad, Graeme; Perrier, Sébastien; Zetterlund, Per B.
ABSTRACT: It is demonstrated that the degree of livingness (chain‐end fidelity) in RAFT polymerization for a given degree of polymerization can be markedly increased in miniemulsion polymerization relative to the corresponding homogeneous bulk system. Polymerization of styrene was conducted using a poly(methyl methacrylate) benzodithioate as macroRAFT agent in both miniemulsion and bulk. The substantially higher polymerization rate in miniemulsion, which is attributed to the segregation effect (compartmentalization) causing a reduction in the rate of bimolecular termination, makes it possible to reach a given degree of polymerization in a significantly shorter time than in the corresponding bulk system. As a consequence, fewer initiating radicals are required throughout the polymerization, leading to higher livingness in the more rapid miniemulsion system. It is demonstrated how this approach facilitates synthesis of high‐molecular‐weight block copolymers comprising slowly propagating monomers such as styrene and methacrylates. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 1938–1946 Abstract : The degree of livingness in RAFT polymerization for a given degree of polymerization can be markedly increased in miniemulsion polymerization relative to the corresponding homogeneous bulk system. The higher polymerization rate in miniemulsion, attributed to the segregation effect (compartmentalization), makes it possible to reach a given degree of polymerization in a significantly shorter time. This approach facilitates synthesis of high‐molecular‐weight block copolymers comprising slowly propagating monomers such as styrene and methacrylates.